SIGNIFICANT AND INSIGNIFICANT SEMES IN LINGUISTIC ANALYSIS (International Educators Conference, 2025)
The article explores the distinction between relevant and irrelevant semes in English and Uzbek. It focuses on how relevant semes contribute to the core semantic structure of a word, whereas irrelevant semes provide supplementary or context-dependent information. The study examines how these semes are realized lexically, contextually, and pragmatically across both languages..